Akibat Hukum dalam Perkawinan yang Dilakukan oleh Suami Tanpa Ijin Istri Sahnya - Barzah Latupono (Faculty of Law, Universitas Pattimura, 2020)
Marriage is a very sacred bond. The purpose of this research is to study and analyze the existence of household life phenomena that occur misunderstandings, disputes, quarrels, which are prolonged, which trigger a break in the relationship between husband and wife, but there are also disputes in the household but do not break the relationship in the sense of divorce but the husband has an affair. The research method used in this research is normative legal research, with a statutory approach, conceptual approach and case approach. The results of the research show that the husband performs the next marriage, it is permissible in Islamic law as long as there is honesty and permission from the first wife, but if a marriage is carried out secretly without the permission of the first wife then this marriage will bring harm to the parties and this kind of marriage will not will be recognized by religious law and State law which will result in the parties not getting recognition and protection by law because the marriage is considered invalid and can be canceled.